Диференціaція судинної обкладинки та мезофілу у С3 і С4 видів рослин у зв’язку з оптимізацією фотосинтезу - Кравець, О.А.; Горюнова, І.І.; Ємець, А.І.; Блюм, Я.Б. (Фактори експериментальної еволюції організмів, 2015)
Aims. The comparative anatomical study of the bundle sheath and mesophyll in C3 and C4 species to determine the changes in leaf anatomy that cause the formation of two-chamber C4 system named Kranz anatomy. Methods. Light and fl uorescent microscopy. Results. Anatomical features of C3 and C4 plants is a refl ection of the various ways of differentiation of leaf tissues (bundle sheath and mesophyll cells). In monocots C3 plants the functioning of the photosynthetic apparatus is accompanied by specialization and complexity of the bundle sheath, namely the formation of additional mestomic bundle sheath, cutynization of the cell walls, “lengthening” of bundle sheath cells to the leaf surface and the development of air parenchyma. The simplifi cation of the bundle sheath structure (reduction of mestomic cover and its «lengthening») and differentiation of mesophyll to the Rubisco-containing bundle sheath and FEPK-enriched mesophyll chloroplasts occur by formation of C4 metabolism. Conclusions. C3 and C4 plants use different ways of CO2 concentration and assimilates of the bundle sheath cells. Structural adjustment of C4 plants are more advanced: grow of effective space of vien and bundle sheath while area of mesophill cells are reduced. The mesophill cells are characterized by expressive dynamic properties than the bundle sheath. Veins become the inductors of Kranz anatomy while hlorenhima cells serve as a source of CO2 and the «buffer zone». Keywords: leaf veins, bundle sheath, mesophyll cells, Kranz anatomy, C3 and C4 species.